ANALYSIS OF THE INFLUENCE OF ELECTRONIC WORD OF MOUTH ON PURCHASE DECISIONS FOR BUTTONSCARVES - Rosliana Sinambela, Nia; Arto Pujangkoro, Sugih; Helmi Situmorang, Syafrizal (Universitas Islam Lamongan, 2024)
Electronic Word Of Mouth is used as a means of communication between people where the person receives non-commercial messages about brands, products or services. With the existence of Electronic Word Of Mouth, it is easier for prospective buyers to determine their choice whether to buy the product or not depending on the content of the information whether it is positive or negative. In addition to Electronic Word Of Mouth, prospective buyers generally adjust their own personality to the personality of an item being purchased. This type of research uses a quantitative method by distributing questionnaires via Google Formal. The population used in this study were Buttonscarves buyers at Sun Plaza and Delipark. The sampling technique in this study used the purposive sampling technique with a sample size of 175 respondents divided into 88 respondents at Sun Plaza and 87 respondents at Delipark. The results of this study are that Electronic Word Of Mouth has a positive and significant effect on the decision to purchase Buttonscarves products. Electronic Word Of Mouth has a positive and significant effect on the decision to purchase the results of the determination test obtained R2 of 0.56 or 56%.This explains that around 56% of purchasing decision variables can be explained by EWOM variables.